Isolation of betulinic acid and antioxidant and anti-HIV-1 reverse transcriptase activity of Cratoxylum formosum subsp. pruniflorum (Kurz) Gogelein extract - Srisombat, Nattawut; Bapia, Sorawit; Ratanabunyong, Siriluk; Choowongkomon, Kiattawee; Vajrodaya, Srunya; Duangsrisai, Sutsawat (Agriculture and Natural Resources, 2019)
Cratoxylum formosum subsp. pruniflorum (Kurz) Gogelein has been used as a medicinal plant for the treatment of many diseases. C. formosum bark was macerated with methanol and partitioned using hexane and chloroform. The chloroform bark extract was fractionated using column chromatography. Five combined fractions were obtained (CFA–CFE) and then investigated for antioxidant activity based on the total phenolic content (TPC), total flavonoids content (TFC), ferric reducing antioxidant power (FRAP) and nitric oxide (NO) radical scavenging activity and also for anti-HIV-1 reverse transcriptase (RT) activity. CFE had the highest antioxidant activity, with values for TPC, TFC and FRAP of 44.84 ± 0.05 μg of gallic acid equivalents/g, 580.69 ± 0.78 μg of quercetin equivalents/g and 82.56 ± 0.08 μg of Trolox equivalents/g of dry weight extract, respectively, and CFB inhibited the nitric oxide radical at the lowest concentration (96.73 μg/mL). However, the methanolic bark extract, fractions CFC, CFD and CFE had high inhibitory effects against HIV-1 RT with values greater than 60% relative inhibition. CFE had the highest percentage relative inhibition among the fractions and was at a comparable level to a standard drug (Nevirapine). The ranking of the antioxidant and anti-HIV-1 RT activities of the fractions was CFE followed by CFD, CFC, CFB and CFA, respectively. Betulinic acid was isolated from fraction 52 of the chloroform extract that was eluted with chloroform-acetone (1:9, volume per volume). The 1H and 13C nuclear magnetic resonance data obtained were in accordance with the previous published data. There is a need for further isolation of bioactive compounds and evaluation of their antioxidant and anti-HIV activities.